A Pragmatic Analysis on Organic Field-Effect Transistors: Advances and Applications (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2024)
The paper reviews recent publications on organic field-effect transistors (OFETs), focusing on the structural and electrical properties of materials used in their construction. It has been found that in partially ordered systems, charge transport is dominated by thermally activated, field-assisted hopping between disorder-induced localized states, rather than intrinsic polaronic hopping seen in organic single crystals. Significant research has also been directed toward developing air-stable organic semiconductors through solution processing, which can produce OFETs with excellent properties and stability under repeated testing and continuous electrical bias. Recent experiments have shown ambipolar channel conduction and light emission in conjugated polymer FETs, laying the groundwork for OLED-based displays driven by active matrix OFETs.